Higher-than-optimal body mass index and diabetes mortality in the Asia Pacific region - Martiniuk, A.; Lee, Crystal; Colagiuri, S.; Woodward, M. (Elsevier Ireland Ltd, 2011)
Aims: To estimate the population attributable fraction (PAF) of elevated body mass index (BMI) for diabetes mortality by country, sex and age group, for the Western Pacific and South-East Asia regions. Methods: Published data on nationally representative mean BMI (since year 2000) and age-specific hazard ratios for death due to diabetes for a unit increase in BMI were used to calculate PAFs using the methodology of the WHO Global Burden of Disease project, taking a BMI of 21kg/m 2 as the ideal. Results: Data were available for 15 countries in the Western Pacific and South East Asia regions. This included data from 330,374 individuals. Age-standardized male PAFs ranged from 11% for India to 98% for American Samoa. Age-standardized female PAFs ranged from 9% in India to 95% in American Samoa. For males, several countries had PAFs at or below 30% - these were India, Indonesia and Japan; whereas, India and Indonesia were the only two countries with PAFs below approximately 30% for females. Conclusion: Although this study is not a trial and thus not able to definitively state the proportions of diabetes deaths that could be averted by reducing mean BMI, this paper demonstrates that theoretically between 9% and 98% of deaths from diabetes could be prevented by tackling obesity in the Asia Pacific region. Preventing these deaths is likely to have an enormous positive social and economic impact, particularly in this region consisting of many low and middle-income countries.